2018
DOI: 10.1002/ece3.3928
|View full text |Cite
|
Sign up to set email alerts
|

Use of field‐portable ultrasonography reveals differences in developmental phenology and maternal egg provisioning in two sympatric viviparous snakes

Abstract: A thorough understanding of the life cycles underlying the demography of wild species is limited by the difficulty of observing hidden life‐history traits, such as embryonic development. Major aspects of embryonic development, such as the rate and timing of development, and maternal–fetal interactions can be critical features of early‐life fitness and may impact population trends via effects on individual survival. While information on development in wild snakes and lizards is particularly limited, the repeate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 66 publications
(106 reference statements)
0
10
0
1
Order By: Relevance
“…25 days among years, shortening or extending the time available for post‐natal growth accordingly. Unfortunately, accurate estimates of the timing of ovulation and parturition are difficult to obtain and are likely to vary among individuals in the field (but see Sparkman et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 days among years, shortening or extending the time available for post‐natal growth accordingly. Unfortunately, accurate estimates of the timing of ovulation and parturition are difficult to obtain and are likely to vary among individuals in the field (but see Sparkman et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…25 days among years, shortening or extending the time available for post-natal growth accordingly. Unfortunately, accurate estimates of the timing of ovulation and parturition are difficult to obtain and are likely to vary among individuals in the field (but seeSparkman et al, 2018).Cohort effects at my study site were of sufficient magnitude to accelerate attainment of reproductive maturity in at least some individuals during warm years. For example, in 2010, the end-of-season SVL of S. dekayi neonates (185.5 mm) exceeded the minimum SVL of reproductively mature males (175 mm based on presence of sperm in cloacal smears, personal observation) and at least some neonatal males exceeded 175 mm in 2010, 2014, 2016, and 2018.…”
mentioning
confidence: 91%
“…Previous studies examining trade-offs between maternal and embryonic hydration during water deprivation concluded that maternal hydration is compromised in favor of embryonic hydration (Dupoué et al, 2015, Sparkman et al, 2018. However, these studies relied on egg…”
Section: Discussionmentioning
confidence: 99%
“…For a number of reasons, the best approach will depend on the circumstances, and may differ between amphibians and reptiles. For instance, assessing morphological features of embryos in transparent amphibian eggs can sometimes be done visually without impeding development, whereas in reptiles, assessment usually involves sacrificing embryos (but see Sparkman et al, 2018 on reptilian ultrasound), such that different methodologies may be favored in each group.…”
Section: Best Practices For Measuring Thermal Variables In Studies Ofmentioning
confidence: 99%